2005
DOI: 10.1002/fuce.200400083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silicotungstic Acid (STA) on the Performance of a Polymer Electrolyte Fuel Cell (PEMFC) Based on Nafion® Cast in Dimethylformamide

Abstract: A casting process for composite Nafion®/STA membranes was achieved. The membrane casting was based on the evaporation of 5% Nafion® solution in N,N′‐dimethylformamide (DMF) with and without silicotungstic acid (STA) as an additive. Optimized parameters for the casting process were determined. The water uptake and the ionic conductivity of the cast membranes were measured. The variation of the volume of Nafion® and the STA concentrations on the water uptake and conductivity of the cast membranes were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…They reported that the maximum power density for a SiW 4À -based membrane was even lower than that for a bare Naon®-silica membrane. Tian and Savadogo 19,20 fabricated a Naon®/SiW 4À composite membrane with different concentrations of SiW 4À . The water uptake of the SiW 4À doped membrane was signicantly higher than that of Naon® 117 and increased with the SiW 4À concentration.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the maximum power density for a SiW 4À -based membrane was even lower than that for a bare Naon®-silica membrane. Tian and Savadogo 19,20 fabricated a Naon®/SiW 4À composite membrane with different concentrations of SiW 4À . The water uptake of the SiW 4À doped membrane was signicantly higher than that of Naon® 117 and increased with the SiW 4À concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Cast membranes have also been used in the production of self-humidifying membranes, where hygroscopic oxides, such as SiO 2 [12] TiO 2 [13], silicotungstic acid (STA) [14] and SiO 2 + TiO 2 + nanocrystallites of Pt [15], have been incorporated into the polymer matrix. The platinum provides a catalytic site for the combination of H 2 and O 2 while the water produced is retained by the hygroscopic oxides, providing a low electrical resistance and reduced crossover.…”
Section: Introductionmentioning
confidence: 99%
“…The latter membrane compared favorably with recast Nafion ® , which had an areaspecific resistance of 0.19 Ω cm -2 under the same conditions. Savadogo and co-workers (Savadogo, 2004;Tazi & Savadogo, 2000Tian & Savadogo, 2005) prepared composite www.intechopen.com membranes constituted of recast Nafion ® and mixed with appropriate concentration of HPA, namely, silicotungstic acid (STA), phosphotungstic acid (PTA) and phosphomolybdic acid (PMA). It was shown that the water uptake of the various membranes increases in this order: Nafion ® 117 (27%) < Nafion ® /STA (60%) < Nafion ® /PTA (70%) < Nafion ® /PMA (95%).…”
Section: Organic/heteropolyacid (Hpa) Nanocomposite Membranesmentioning
confidence: 99%